2019
DOI: 10.1039/c8qo01289j
|View full text |Cite
|
Sign up to set email alerts
|

n-Butyllithium catalyzed hydroboration of imines and alkynes

Abstract: Simple and convenient n-BuLi is reported as a highly efficient catalyst in promoting the hydroboration of imines and alkynes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(38 citation statements)
references
References 69 publications
1
37
0
Order By: Relevance
“…Nevertheless, Bao and Shi recently expanded its utility in the hydroboration of allylic alcohols, 120 alkenes, alkynes, and imines. 121,122 Meanwhile, An and co-workers disclosed an example of hydroboration of aldehydes and ketones in the presence of sodium hydride at rt, to give corresponding alcohols (after hydrolysis) in almost quantitative yields (Scheme 16). 123 A considerable drawback of this protocol is again connected to the sensitivity of the catalyst.…”
Section: Hydroboration Of Unsaturated Carbon-heteroatom (O N) Moietiesmentioning
confidence: 99%
“…Nevertheless, Bao and Shi recently expanded its utility in the hydroboration of allylic alcohols, 120 alkenes, alkynes, and imines. 121,122 Meanwhile, An and co-workers disclosed an example of hydroboration of aldehydes and ketones in the presence of sodium hydride at rt, to give corresponding alcohols (after hydrolysis) in almost quantitative yields (Scheme 16). 123 A considerable drawback of this protocol is again connected to the sensitivity of the catalyst.…”
Section: Hydroboration Of Unsaturated Carbon-heteroatom (O N) Moietiesmentioning
confidence: 99%
“…Together with the transition metal-free organocatalysts for the hydroboration of alkynes, environmentally benign and commercially useful main-group catalysts based on Al, 90,[130][131][132][133][134][135][136][137][138][139] Li, [138][139][140][141][142] and Mg 143,144 have been recently developed as alternatives to transition metal catalysts. 145 In 2016, Roesky et al reported the cis-hydroboration of alkynes catalyzed by a neutral DEP NacNacAlH 2 (18).…”
Section: Hydroborationmentioning
confidence: 99%
“…Recently, the groups of Xue 140 and Xu 141 independently demonstrated that highly basic and commercially available n-BuLi (30) catalyzes the cis-hydroboration of terminal and internal alkynes to produce the b-trans-alkenyl boronic esters (Scheme 46). Under the n-BuLi (30) catalytic system, terminal alkynes were hydroborated with HBpin in neat conditions at 25 C, while the hydroboration of (un)symmetrical internal alkynes occurred at 130 C to give a mixture of regio-or stereoisomers of the vinyl products.…”
Section: Hydroborationmentioning
confidence: 99%
“…12 Recently, Zhu’s group reported protocols for the catalytic hydroboration of aldehydes, ketones, imines, and alkynes with n -BuLi. 13 More recently, the Leung group has reported catalyst-free and solvent-free hydroboration of ketones at an elevated temperature. 14 These results point toward strong possibility for the development of more efficient and eco-friendly conditions for the catalytic hydroboration of carbonyl compounds without the need for highly toxic metals and costly ligands, which is the objective of our present study.…”
Section: Introductionmentioning
confidence: 99%